Hubungan Faktor Risiko Lingkungan Fisik Rumah dan Perilaku Kesehatan dengan Kejadian TB Paru di Wilayah Kerja UPT Puskesmas Bandar Khalifah Deli Serdang - Syahri, Alfiya; Nanda, Meutia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Pulmonary TB cases at the Bandar Khalifah Health Center increased in 2021 by 219 cases, while in 2022 there were 268 cases. This study aims to determine the risk factors of the physical environment of the house and health behavior with the incidence of Pulmonary TB in the Working Area of UPT Puskesmas Bandar Khalifah Deli Serdang. This study used a case control design, with a sample of 120 people consisting of 60 cases and 60 controls. Using univariate and bivariate analysis. The results of the bivariate analysis showed a significant relationship between occupancy density (p value = 0.009, OR= 2.891), ventilation (p value = 0.010, OR= 0.351), lighting (p value = 0.045, OR= 2.486) and the presence of room windows (p value = 0.026, OR= 0.660) with the incidence of Pulmonary TB in the working area of the Bandar Khalifah Health Center. Meanwhile, knowledge (p value = 0.231, OR= 0.229), attitude (p value = 0.778, OR= 0.351), and floor type (p value = 0.601, OR= 0.660) were not related to the incidence of Pulmonary TB in the working area of the Bandar Khalifah Health Center. Keywords: Risk factor; Incidence of Pulmonary TB